The trinitarian theology of Saint Thomas Aquinas - Emery, Gilles (Oxford University Press, 2007)
"This is an introduction to Thomas Aquinas' Trinitarian theology as a whole, and an analysis of the treatise of the Trinity within the Summa Theologiae. It is written both for students and beginner readers of the treatise, and for anyone who has dipped into one or two of the questions and realized that they need a general overview of their intellectual context and of the historical debates which lie behind them."--Jacket